EKSPLORASI KESIAPAN UMKM KOTA SERANG DALAM MENERAPKAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO, KECIL, DAN MENENGAH (SAK EMKM) - Komarudin, Mochamad Fahru; Pebrianti, Pebrianti; Afriani, Raden Irna (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2026)
This study aims to explore the readiness of MSMEs in Serang City in implementing the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). The study employed a descriptive qualitative approach using interviews, observations, and documentation as data collection techniques. Data analysis was conducted using NVivo software to identify the main research themes. The results showed that the readiness of MSMEs in Serang City is still at a developing stage. Most business owners understand the importance of financial recording, but they do not yet fully understand the technical implementation of SAK EMKM. The main obstacles found include low accounting literacy, limited time, lack of administrative staff, insufficient training, and suboptimal use of digital technology. However, most MSME owners showed willingness to adopt better financial recording systems if practical and continuous assistance is provided. This study concludes that the implementation of SAK EMKM among MSMEs in Serang City requires support from local government, academics, and related institutions through training programs, mentoring, and digitalization of financial records. The findings are expected to serve as a policy basis for improving financial management quality and MSME competitiveness in the region.